INCREASING QUALITY OF PRODUCTION AND MARKET ACCESS FOR COFFEE FARMING GROUPS THROUGH BEHAVIOR CHANGES AND HARVEST MANAGEMENT - Yudha, Aditya Prima (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2021)
Indonesia is one of the largest coffee producer countries in the world after Brazil, Colombia and Vietnam. For the local market, domestic coffee consumption continues to increase every year. This growing industry and large market are not necessarily enjoyed by coffee farmers. The problem that occurs is that coffee farmers do not have sufficient knowledge, information and distribution channels for their crops. Coffee farmers dependence on middlemen, blocking their access to other market potentials. As a result, the welfare of coffee farmers is generally still very low, due to the low selling price of their crops and the debt bondage to middlemen. This problem also occurs in a group of coffee farmers in Megamendung village, Bogor Regency. The Megamendung area is one of the centers for robusta coffee plantations in Bogor. Coaching coffee farmers with education on improving the quality of production and opening market access for product sharing is expected to be a solution to improving the welfare of coffee farmers in Megamendung village. Community service activities include 1) Survey and discussion of the service team with coffee farmer partners 2) Training on good coffee cultivation and harvesting materials 3) Sorting and packaging training 4). Marketing of crops to end users.